Evaluation of Coal Based Granular Activated Carbon for Removal of Manganese(II) from Wastewater - Gawande, N.J.; Chaudhari, A.R.; Khope, R.U. (Asian Journal of Chemistry, 2012)
In present study coal based carbon filtrasorb 816 (F-816) and filtrasorb 300 (F-300) were tested for their efficiency in removing metal ions from aqueous phase. Studies on removal of manganese(II) from aqueous phase by adsorption on granular activated carbon containing adsorbed organic ligand such as resorcinol have been carried at constant temperature 25 ± 0.5 ºC. The present study deals with the determination of manganese(II) removal capacity from synthetically prepared industrial wastewater using these low cost adsorbents. The adsorption isotherms of manganese(II) on Granular activated carbon have been determined at pH in the range of 5 to 6. Freundlich and Langmuir isotherm models were applied to the equilibrium data. The data could be fitted reasonably well to these both isotherms. Experimental results demostrate that the F- 816 has a significant capacity for adsorption of manganese(II) as compared to F-300 from wastewater.